Temperature scaling of dynamic hysteresis in soft lead zirconate titanate bulk ceramic - Yimnirun R. (2014)
The temperature scaling of the dynamic hysteresis was investigated in soft ferroelectric bulk ceramic. The power-law temperature scaling relations were obtained for hystersis area 〈A〉 and remnant polarization Pr, while the coercivity EC was found to scale linearly with temperature T. The three temperature scaling relations were also field dependent. At fixed field amplitude E0, the scaling relations take the forms of 〈A〉 T-1.1024, Pr T-1.2322, and (EC0 - EC) T. Furthermore, the product of Pr and EC also provides the same scaling law on the T dependence in comparison with 〈A〉. © 2007 American Institute of Physics.